Canada: Peary Arctic Club, 1898-1902, Peary's tent at Fort Conger - Peary, Robert E. (Robert Edwin), 1856-1920 (1898)
Peary's tent at Ft Conger (Winter quarters 1900-1901) http://www.matthewhenson.com/1909NPtrip/1910b.html